Experimental study of heat exchange processes in heat exchangers of a new design for cooling supply air in poultry houses with water from underground wells - Trokhaniak, V.; Gorobets, V. (Energy and Automation, 2023)
In this work, an experimental installation for cooling air in a poultry house was developed and manufactured using a new design of a heat exchanger-recuperator, in which water from underground wells is used as a cooling medium. The schematic diagram of the heat exchanger installation and device is described, and the characteristics of the measuring instruments are given. Experimental studies of heat exchange processes in the heat exchanger were carried out and the temperature distributions in the cold and hot coolants were determined, the Nusselt number and the heat transfer coefficient on the surface of the tube bundle were found. It is shown that the use of a new design of compact tube bundles makes it possible to increase the heat transfer coefficient by 33 %. Based on the statistical analysis, the results of numerical model calculations are compared with experimental data on the heat transfer of pipe bundles. The error obtained in the results of numerical modeling is slightly more than 5 %. Key words: experiment, heat exchanger, heat transfer, intertube channels, weight and dimensions